Analisis Konsumsi Bahan Bakar Kapal Niaga Berdasarkan American Society for Testing Materials the Institute of Petroleum (ASTM-IP) - Nafi Almuzani; Bambang Wahyudi; Imam Fachruddin (Dinamika Bahari, 2020)
Vessel operational costs are dominated by fuel purchases. Furthermore, monitoring the consumption of fuel oil on the ship is not given enough attention, because the officers concentrate more on how the ship can move to its destination. The purpose of this study is to determine the correction that must be done as well as the impact caused if the consumption of fuel oil through the flowmeter on the ship is corrected using ASTM-IP. The subjects of this study were four vessels in the PT. S. I. Ship Management with specific graphity (SG) of 0.9601. From the results of the study show the output data flowmeter on the main engine must be multiplied by the factor for reducting the volume to 15o C in ASTM-IP so that it has an impact on the accuracy in reporting fuel consumption. As a result operational costs are reduced and the ship company can sell its services competitively